Control of sexual reproduction in Aspergillus species - Ashour, Adel (2014)
The principal aim of the present study was to investigate biochemical, evolutionary and genetic factors that influence and control sexual reproduction in Aspergillus species. The aspergilli include species of major economic and medical importance, with some species reproducing by sexual means but many being only known to reproduce by asexual means. It was anticipated that an improved understanding of the factors controlling sexual reproduction would provide fundamental insights into biological processes controlling sex in ascomycete fungi as a whole, as well as providing insights to enable methods to be designed to promote sexual reproduction in the laboratory. The sexual cycle could then be used in classical genetic studies and strain improvement programmes. Studies were focussed mainly on three representative Aspergillus species, namely the homothallic (self fertile) Aspergillus nidulans, Eurotium repens and Neosartorya fischeri. Several isolates were obtained from different worldwide locations and their identity verified by phylogenetic means prior to main experimental work. Firstly, conditions were optimised for both sexual and asexual reproduction for each species to facilitate later experimental work. This involved growth under a variety of different environmental parameters including media type, temperature, light, dark, sealing or non-sealing of plates, and incubation in variable stack number, Interestingly it was found that highest levels of cleistothecia of the model species A. nidulans were produced at 32ºC, rather than the 37ºC routinely used in laboratories worldwide, and by incubating plates in a single layer. Secondly, investigations were made to assess whether asexual conidia and sexual ascospores of A. nidulans exhibited differential resistance to environmental stress, which might be of importance for the evolutionary maintenance of different forms of reproduction in this species. Conidia and ascospores from a variety of isolates and strains were subjected to thermal stress, involving exposure to a range of temperatures between 50ºC and 75ºC for 30 min, and in addition to UV radiation stress, involving exposure to 254 nm for different time points between 10 and 60 min. Spore viability data for both heat and UV shock was converted to D-values, revealing that ascospores were slightly more resistant than conidia to thermal shock and had markedly greater resistance to UV shock. These results help to explain why homothallism might be retained in species that are able to produce asexual spores at much lower metabolic cost. Parallel studies with E. repens also showed that ascospores exhibited higher thermal resistance than conidia. Thirdly, the possible evolution of asexuality was studied. Previous classic work by Mather and Jinks (1958) suggested that a gradual loss of sexuality occurs when fungi are subcultured solely by asexual transfer. This claim was tested by serial asexual transfer and subsequent assessment of sexual potential for a variety of A. nidulans, E. repens and N. fischeri isolates and strains. A ‘slow decline’ in sexual fertility was indeed observed in the majority when repeatedly subcultured by asexual conidia. Staining with Hoechst 33258 and Calcofluor was used to correlate the number of mitotic divisions occurred in the apical cells with the decrease in sexual fertility for all three species. Significantly, it was found that the sexual fertility of most long-term asexual strains could be restored either partly of fully back to initial levels by propagation by ascospore transfer. This suggested that a mixture of epigenetic and mutational factors might be partly responsible for the evolution of asexuality in fungi. Finally, investigations were made to identify novel genes involved in the regulation of sexual fertility in the aspergilli. A series of gene disruption cassettes were used to delete putative high-mobility group transcription factors from the genome of A. nidulans. Deletion of one particular gene caused a loss of sexual fertility indicating that this gene acts as a sexual regulator. This gene was termed ‘steD’. Complementation work via the sexual cycle confirmed that sex could be restored by restoration of this gene. This discovery indicated that many so far unidentified genes are likely to have key roles regulating sexual fertility of A. nidulans and ascomycete fungi in general. Thus, the loss of function of a wide range of genes might lead to the evolution of asexuality in ascomycete fungi.